Oxidative Degradation of Phenol by Corona Dielectric Barrier Discharge at Gas-Liquid Interphase - Wang, Lei; Yu, Xin; Li, Guoxin; Li, Dailin (Asian Journal of Chemistry, 2014)
In this study, corona gas-liquid dielectric barrier discharge reactor for phenol degradation was investigated. The discharge was formed between two needle metal electrodes and an aqueous solution surface where the counter electrode was submerged and separated by a quartz dielectric tube. Effects of solution conductivity, pH and gas composition on the degradation were examined. Experimental results showed that the degradation of phenol proceeded perfectly in a wide range of solution conductivity. In the process of degradation of phenol, ozone was additionally formed. The removal of phenol increased with the order: argon < air < oxygen. Increasing pH was favorable for phenol removal. When using argon as the discharge gas, the major degradation products were catechol, hydroquinone, hydroxyhydroquinone, acetic acid, formic acid and oxalic acid. In oxygen or air discharges, 1,4-benzoquinone and muconic acid were additionally formed. The energy efficiency of removal of phenol has been compared with other competitive processes.